A gyro-enhanced smart-phone framework to develop motion-based user interfaces for animation and virtual environments - Pereira, Tiago (2020)
In this paper, the mobile phone is presented as an alternative device to interact with animation systems and virtual environments, including video games. Basically, we show how the gyroscope of a mobile device can work as a sensor to control the pose and motion of a mobile device controlled object or character in a 3D virtual world. More specifically, we introduce a framework that enables the development and rapid prototyping of motion-based user interfaces for animation systems and virtual environments. This framework provides tools to capture and control the motion of mobile devices-binded objects in a 3D virtual scene over a wireless communication channel via a simple, fast and efficient protocol named Open Sound Control (OSC).